Geographies of corporate philanthropy: The Northern Rock Foundation. (March 2018) - Marshall, Neill; Dawley, Stuart; Pike, Andy; Pollard, Jane
The paper contributes to literature on the geographies of corporate philanthropy through a case study of the origins, growth and decline of the Northern Rock bank's charitable foundation. Analysis reveals the complex, geographically-embedded nature of philanthropic motivations and impacts. It demonstrates that investment in home and community by philanthropists was part of a regionally-inscribed business-model of excessive risk taking that brought them considerable personal financial rewards. It highlights tensions and conflicts between corporate philanthropists and professional grant-makers over the scale and regional focus of giving. The paper concludes that the positive outcomes of corporate philanthropy are difficult to sustain in disadvantaged regions where shifts in corporate strategy and fragilities in the local economy undermine charitable giving.